Managing anemia in lymphoma and multiple myeloma - Gunnar Birgegård (Dove Medical Press, 2008)
Gunnar BirgegårdDepartment of Haematology, University Hospital, Uppsala, SwedenAbstract: Anemia is common in cancer, and lymphoproliferative disease is no exception. Erythropoiesis-stimulating agents (ESA) have been used for renal anemia since 1986, and considerably later in cancer anemia. The first studies were published around 1993, but the use of ESA did not become common in cancer anemia until in the late 1990s. Cancer anemia is still under-treated. This review gives an overview of the use of ESA in hematologic malignancies. A background is given about this treatment in the cancer field generally. The pathophysiology of cancer anemia is described with special emphasis on the disturbances in iron metabolism. Functional iron deficiency has been shown to be both frequent and important as a hindrance for response to ESA treatment, and recent studies are reported in some detail, where the use of intravenous iron was shown to improve the response rate of ESA treatment.Keywords: Epo, epoetin, ESA, cancer anemia, lymphoma, myeloma, lymphoproliferative disease